ANALISIS TINGKAT PRODUKTIVITAS DAN KOLABORASI PENULIS PADA JURNAL PERPUSTAKAAN PERTANIAN KEMENTERIAN PERTANIAN REPUBLIK INDONESIA PERIODE TAHUN 2017-2021 : Kajian Bibliometrika: Kajian Bibliometrika - Yunus Winoto (IJAL (Indonesian Journal of Academic Librarianship), 2024)
ABSTRACT This study aims to determine the level of productivity and collaboration of writers in the agricultural library journal Ministry of the Republic of Indonesia (JPP) during the 2017-2021 publication period. The method used in this study uses bibliometric analysis, namely by examining each article and recording all information related to the profile of the article (such as the number of articles and references used), noting the names of the authors along with the title of the article written in each issue number, as well as record the agency of origin and profession of the author. The articles in this study started with the issue of Vo 26 No. 1 of 2017 up to volume 30 number 1 of 2021 with a total of 50 articles. Based on the research results, it is known that the value of collaboration is at a value of 0.48, namely C less than 0.5, which means that articles written individually in the journal are still larger than articles written in collaboration. Meanwhile, regarding the productivity of the author, it can be seen from the year, namely in 2020 with a total of 23 authors. While the name of the most prolific writer is Heryati Suryantini with the number of articles produced around 6 articles.